Video Tracking dalam Digital Compositing untuk Paska Produksi Video - Ardiyan, Ardiyan (Bina Nusantara University, 2012)
Video Tracking is one of the processes in video postproduction and motion picture digitally. The ability of video tracking method in the production is helpful to realize the concept of the visual. It is considered in the process of visual effects making. This paper presents how the tracking process and its benefits in visual needs, especially for video and motion picture production. Some of the things involved in the process of tracking such as failure to do so are made clear in this discussion.